Rectal obstruction due to endometriosis: A case report and review of the Japanese literature - Ono, Hiromi (Int J Surg Case Rep, 2014)
INTRODUCTION: Colorectal obstructive endometriosis is relatively rare in Japan and its differentiation from malignancy is often difficult. We report a case of rectal obstructive endometriosis. PRESENTATION OF CASE: A 37-year-old woman was referred to our hospital with a suspected ileus. Her chief symptoms were left lower abdominal pain and vomiting. Colonoscopy showed an intraluminal mass of redness in the upper rectum. A proctectomy was performed because of the bowel obstruction. The rectum was filled with an intraluminal mass measuring 5 cm × 4 cm, and endometriosis was diagnosed pathologically. DISCUSSION: A preoperative diagnosis of colorectal obstructive endometriosis is often difficult because of the lack of definite diagnostic, clinical, sonographic, or radiological findings that are characteristic of this disease. Medical treatment is not always effective for colorectal obstructive endometriosis, and surgery is often performed. CONCLUSION: Colorectal obstructive endometriosis should be considered as a differential diagnosis in cases of various gastrointestinal symptoms in women who are of reproductive age.